1981
DOI: 10.1084/jem.153.4.1004
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal treatment with low doses of anti-idiotypic antibody leads to the expression of a silent clone.

Abstract: BALB/c mice immunized with bacterial levan (BL) produce an immune response that fails to generate antibody expressing the idiotype (Id) of the beta (2 leads to 6) fructosan-binding myeloma protein ABPC 48 (A48). Pretreatment of newborn BALB/c mice (at 1 d of age) with 0.01-10 microgram of affinity purified BALB/c anti-A48 Id antibody followed by immunization with BL 1-2 mo later produces an anti-BL response that expresses the A48 Id. This shows that A48 Id+ anti-BL clones belong to a normally silent fraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
3

Year Published

1983
1983
1994
1994

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 13 publications
3
36
0
3
Order By: Relevance
“…In the past, it has been the general case that clonotypes and families of clonotypes that can be identified in one strain are often either absent or present in much lower frequencies in other murine strains, particularly strains that differ in the Ig heavy chain gene locus (25)(26)(27)(28)(29)(30)(31)(32)(33), and, where appropriate, the light chain gene locus (54). In the majority of cases, such disparities appear to be not absolute but rather quantitative (17,18,(46)(47)(48)(49)(50). However, with rare exceptions (53), it remains unknown whether indistinguishable clonotypes present in two distinct strains are completely identical at the amino-acid sequence level, and whether genes expressing equivalent clonotypes in different strains are actually alleles of one another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, it has been the general case that clonotypes and families of clonotypes that can be identified in one strain are often either absent or present in much lower frequencies in other murine strains, particularly strains that differ in the Ig heavy chain gene locus (25)(26)(27)(28)(29)(30)(31)(32)(33), and, where appropriate, the light chain gene locus (54). In the majority of cases, such disparities appear to be not absolute but rather quantitative (17,18,(46)(47)(48)(49)(50). However, with rare exceptions (53), it remains unknown whether indistinguishable clonotypes present in two distinct strains are completely identical at the amino-acid sequence level, and whether genes expressing equivalent clonotypes in different strains are actually alleles of one another.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies at the phenotypic level have increased our understanding of the mechanisms that regulate this genetic information and determine the expression of each of the many antibody permutations. These mechanisms include tolerance induction (8)(9)(10)(11)(12)(13)(14) and antiidiotypic suppression (15,16) of developing B cell clones, as well as idiotypespecific mechanisms that may be responsible for clonal expansion (17,18).…”
mentioning
confidence: 99%
“…These results suggested that MC1 was probably of the Ab2~ type. The use of Ab2~ as a vaccine candidate is restricted due to the family's inability to induce an antigen-positive response across the species barrier, although their role in modulating the expression of silent clones has been documented (Bona et al, 1981 ;Hiernaux et al, 1981). Ab2fl anti-ids, which can induce an antigenpositive response across the species barrier, have greater potential for vaccine development (Hiernaux, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Jerne's network theory predicts that immune responses are regulated through a series of idiotype-antiidiotype interactions (Jerne, 1974(Jerne, , 1984Cazenave, 1977 ;Urbain et al, 1977;Bona et al, 1981). Idiotypes (or sets of idiotopes) are determinants expressed in the variable region of antibody molecules and lymphocyte antigen receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Os mecanismos de regulação envolvidos no controle da resposta IgE da prole evidenciam que fatores e anticorpos maternos transferidos durante a gestação e amamentação são capazes de diminuir a OVA da imunização neonatal prevenindo a sensibilização da prole (FUSARO et al, 2007, VICTOR et al, 2010. Vários são os mecanismos que os anticorpos IgG anti-OVA maternos podem prevenir ou controlar a sensibilização da prole, seja por formar imunocomplexos com a OVA na imunização da prole; por interagir com receptores inibidores FcγRIIB presentes nos linfócitos B (VICTOR et al, 2010) e DCs; por interações idiotípicas entre o BCR ou TCR de linfócitos regulando a diferenciação em plasmócitos ou controlando a proliferação da células T ao antígeno (HIERNAUX et al, 1981,VAKIL et al, 1986, RIGATO et al, 2009 Em conjunto, estes achados salientam a importância de avaliarmos o efeito da imunização materna no desenvolvimento da resposta imune e da regulação do neonato.…”
Section: Objetivosunclassified